Review: Genetic diversity of local and exotic cattle and their crossbreeding impact on the quality of Indonesian cattle - SUTARNO SUTARNO; AHMAD DWI SETYAWAN (Biodiversitas Journal of Biological Diversity, 2015)
Sutarno, Setyawan AD. 2015. Genetic diversity of local and exotic cattle and their crossbreeding impact on the quality of Indonesian cattle. Biodiversita16: 327-354.Several species of cattle had been domesticated around the world, but only two species werefarmed extensively, zebu cattle (Bos indicus) of the tropics and taurine cattle (Bos taurus) of the subtropical areas. Both of them hadhundreds variety of offspring in the worlds. The third species of cattle that most widely farmed was Bali cattle (Bos javanicus), anindigenous cattle from Indonesia that was domesticated from wild banteng (Bos javanicus javanicus). Besides Bali cattle, Indonesia hadalso some local cattle as direct descendants of or as Crossbreeds of those three cattle. These cattle had been adapted to climaticconditions, feeds and diseases in Indonesia. Local zebu cattle that relatively pure were Peranakan Ongole (PO) or Ongole breeds andSumba Ongole (SO). The main Crossbreed between zebu and Bali cattle was Madura cattle. The other well-known cattle of this wereAceh cattle, Pesisir cattle, Rancah cattle, Jabres cattle, Galekan cattle and Rambon cattle. Crossbreeds of taurine and zebu cattlegenerally produced calf that declining reproductive ability in generations. One fairly successful was Grati cattle or Holstein FreisianIndonesia (FHI) which was a crossbreed of Holstein Friesian and PO cattle. In recent decades, there were many crossbreed activitiesthrough artificial insemination between local cattle and taurine cattle to produce excellent beef cattle, mainly Simmental and Limousin.This activity was carried out widely and evenly distributed throughout Indonesia. It was conducted on all local cattle breeds and wasstrongly supported by local farmers. This crossbreeding activity was feared to change the genetic diversity of local Indonesia cattle,where the descendants could not adapt to the climatic conditions, feeds and localized diseases; and the ability of reproduction continuesto decline in generations, there fore the availability of parental cattle should be maintained continuously. This crossbreed had producedsome new breeds, among others Simpo (Simmental x PO), Limpo (Limousin x PO), Simbal (Simmental x Bali cattle), Limbal(Limousin x Bali cattle), and Madrasin or Limad (Limousin x Madura cattle). Male offsprings were sterile, while female offsprings hadlower reproductive capacity than of the parent’s. This lead to uncertainty over the guarantee of meeting the needs of protein (meat andmilk) of Indonesian in the future, thus there was a need of regulation. On the other hand, in the grasslands of North Australia, thebreeder had produced an eminent cattle breeds, namely Australian Commercial Cattle (ACC), from uncontrolled crossbreeds betweendifferent breedsof taurine and zebu cattle in the pasture, therefore this concerns ignored.